The c-Myc protein induces cell cycle progression and apoptosis through dimerization with Max. - Amati, B (1993)
The c-Myc protein (Myc) is involved in cellular transformation and mitogenesis, but is also a potent inducer of programmed cell death, or apoptosis. Whether these apparently opposite functions are mediated through common or distinct molecular mechanisms remains unclear. Myc and its partner protein, Max, dimerize and bind DNA in vitro and in vivo through basic/helix-loop-helix/leucine zipper motifs (bHLH-LZ). By using complementary leucine zipper mutants (termed MycEG and MaxEG), which dimerize efficiently with each other but not with their wild-type partners, we demonstrate that both cell cycle progression and apoptosis in nontransformed rodent fibroblasts are induced by Myc-Max dimers. MycEG or MaxEG alone are inactive, but co-expression restores ability to prevent withdrawal from the cell cycle and to induce cell death upon removal of growth factors. Thus, Myc can control two alternative cell fates through dimerization with a single partner, Max.